Biomechanical Evaluation of an Augmented Medial Capsular Repair for Hallux Valgus Surgery. Issue 4 (16th October 2019) - Miller, Christopher P.; Paulus, Megan; Kreulen, Christopher; Harris, Thomas; Giza, Eric
Category: Bunion Introduction/Purpose: Hallux valgus correction is often complicated by recurrence in the setting of inadequate soft tissue balancing. The etiology of recurrence is multifactorial, but a key factor is the quality of the medial capsulorrhaphy which is limited by the quality and strength of the soft tissues. These soft tissues are often attenuated with loss of integrity due to the longstanding bunion deformity. We hypothesize that the medial capsulorrhaphy augmented with a suture tape construct will create a stronger repair. Methods: 8 unmatched and 16 matched cadaveric foot specimens were prepared. None had bunion deformities. The 8 unmatched samples were tested to determine the strength of the native medial capsule. The 16 matched samples underwent a longitudinal medial capsulotomy, eminence resection and medial capsulorrhaphy with or without augmentation with a suture tape construct. The samples were then tested in a biomechanics lab to determine the strength of the medial capsulorrhaphy. Results: The mean maximum moment for the intact, capsular repair and suture tape groups were 2.19 ± 0.639 Nm, 0.225 ± 0.074 Nm and 0.968 ± 0.581, respectively, P<0.001. The mean stiffness for the intact, capsular repair and suture tape groups were 8.06 ± 3.75 N/mm, 1.463 ± 0.553 N/mm, and 4.438 ± 4.035 N/mm, respectively, P=0.003. The suture tape provided 4.3x higher maximum moment and 3x higher stiffness compared to traditional medial capsulorrhaphy. Conclusion: The study demonstrates that a medial capsular repair augmented in a cadaveric model of medial capsulorrhaphy to provide greater strength compared to conventional suture repair. Recurrence of hallux valgus after surgery is multifactorial. One element is the strength of the medial imbrication and capsular repair at the 1st metatarsal phalangeal joint (MTPJ). The study presents biomechanical data demonstrating that this repair is strengthened with suture tape augmentation at the medial 1st MTPJ. This may result in decreased recurrence and potentially improved patient satisfaction following bunion correction.